Brd2 inhibits adipogenesis via the ERK1/2 signaling pathway in 3T3-L1 adipocytes. - Kun Zang (Public Library of Science (PLoS), 2013)
Bromodomain-containing protein 2 (Brd2) is a nuclear serine/threonine kinase involved in transcriptional regulation. In 3T3-L1 adipocytes, Brd2 normally co-represses PPARγ (peroxisome proliferator-activated receptor gamma) and inhibits adipogenesis. Here, we show that Brd2 over-expression in preadipocytes inhibits their differentiation into adipocytes, while Brd2 knockdown promotes adipogenic differentiation in vitro and forces cells to undergo adipogenesis independent of the MDI (methyisobutylxanthane, dexamethasone and insulin) induction. In this study, the two key transcription factors for adipogenesis, PPARγ and C/EBPα (CCAAT/enhancer binding protein-α) were persistently expressed during the differentiation of preadipocytes to mature adipocytes in Brd2 knockdown 3T3-L1 cells, but their expression was inhibited in cells in which Brd2 was overexpressed. To investigate the role of Brd2 in signal transduction we examined the expression of several signaling molecules involved in the regulation of gene expression and cell differentiation by immunoblotting assay. Down-regulation of Brd2 expression in 3T3-L1 cells led to a decrease in extracellular signal-regulated kinase1/2 (ERK1/2) activity and, conversely, the up-regulation of Brd2 leads to increase in ERK1/2 phosphorylation. Nevertheless, changes in Brd2 expression do not affect the activities of JNK and p38 MAPK. In addition, the phosphorylation of Rafs is not affected by changes in Brd2 expression in 3T3-L1 cells. MEK inhibitor UO126 partly restores differentiation of 3T3-L1 cells that overexpress Brd2. In conclusion, these results indicate that Brd2 regulates ERK1/2 activity independently of Raf signaling in 3T3-L1 adipocytes.